Long-term somatic embryogenesis and maturation of somatic embryos in Hevea brasiliensis - Cailloux F; Coudret A; Julien-Guerrier J; Linossier L (Plant Science, 1996)
A high frequency of secondary embryogenesis was induced from isolated early cotyledonary-stage somatic embryos of Hevea brasiliensis. A long-term embryogenic line was established by the use of recurrent embryogenesis and maintained for 3 years on hormone-free medium by the transfer of selected proembryogenic masses every 10 days. The addition of 234 mM sucrose as stress with sucrose and 10 -5 M abscisic acid (ABA) to the culture medium enhanced the maturation of somatic embryos. Under these culture conditions, the embryo population was composed of 45;globular, 18;oblong and 37;torpedo-stage embryos. These somatic embryos had well-formed tissue structure, a well-defined epidermis, protein storage bodies, and a high accumulation of starch. The triglyceride content was five times as high in the torpedo-stage embryos that developed on medium supplemented with 234 mM sucrose and 10 -5 M ABA as in embryos obtained on basel medium with 58 mM sucrose.
Keywords: ABA; Hevea brasiliensis; Osmotic stress; Reserve products; Secondary embryogenesis